2019
DOI: 10.1002/acn3.50829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiepileptic drugs in a new TSC/mTOR‐dependent epilepsy mouse model

Abstract: Objective An epilepsy mouse model for Tuberous Sclerosis Complex (TSC) was developed and validated to investigate the mechanisms underlying epileptogenesis. Furthermore, the possible antiepileptogenic properties of commonly used antiepileptic drugs (AEDs) and new compounds were assessed. Methods Tsc1 deletion was induced in CAMK2A‐expressing neurons of adult mice. The antiepileptogenic properties of commonly used AEDs and inhibitors of the mTOR pathways were assessed by EEG recordings and by molecular read out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 65 publications
6
49
0
Order By: Relevance
“…All these changes, together with the enrichment of the mTORC2 downstream signalling pathway, suggest that abnormal expression of PARK7 and GAP-43 might be a result of the dysregulation of the mTOR pathway in the PPS model. Indeed, the mTOR pathway has been shown to be involved in many neurological disorders, such as autism spectrum disorders 47,48 , Alzheimer's disease, tuberous sclerosis complex 46,49,50 , focal cortical dysplasia 51,52 and, more recently, intractable epilepsy 49,[53][54][55][56][57][58] . The mTORC1 and mTORC2 complexes are also upregulated in tissue from patients with MTLE 59 .…”
Section: Discussionmentioning
confidence: 99%
“…All these changes, together with the enrichment of the mTORC2 downstream signalling pathway, suggest that abnormal expression of PARK7 and GAP-43 might be a result of the dysregulation of the mTOR pathway in the PPS model. Indeed, the mTOR pathway has been shown to be involved in many neurological disorders, such as autism spectrum disorders 47,48 , Alzheimer's disease, tuberous sclerosis complex 46,49,50 , focal cortical dysplasia 51,52 and, more recently, intractable epilepsy 49,[53][54][55][56][57][58] . The mTORC1 and mTORC2 complexes are also upregulated in tissue from patients with MTLE 59 .…”
Section: Discussionmentioning
confidence: 99%
“…The ketogenic diet (KD) is a high fat, low carbohydrate regime widely considered an effective non-drug treatment for epilepsy with documented anticonvulsant, antiepileptogenic, and neuroprotective effects on clinically refractory epilepsy and animal models of epilepsy ( Lusardi et al, 2015 ; Simeone et al, 2018 ; Karimzadeh et al, 2019 ). Multiple therapeutic mechanisms have been proposed for KD-induced antiepileptogenesis, including increased adenosine and decreased DNA methylation, reduced mTORC1 activity, and blockade of histone deacetylases ( Koene et al, 2019 ; Boison and Rho, 2020 ). Thus, it is critical to comprehensively assess the molecular changes associated with the KD in epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recently, preclinical evidence suggested that epilepsy severity is directly related to the level of neuronal mTORC1 activity. 5 In a TSC/mTOR-dependent epilepsy mouse model, early treatment with vigabatrin was not able to prevent epileptogenesis, but significantly delayed seizure onset. However, in this preclinical model, epileptogenesis driven by the loss of TSC1 showed a dose-dependent response to the mTORC1 inhibitor, rapamycin.…”
mentioning
confidence: 99%
“…A longitudinal study showed that a cascading risk pathway from gene mutation to cortical tubers and seizure severity in infancy, to poor intellectual outcome in late childhood can be a potential pathogenic mechanism . Recently, preclinical evidence suggested that epilepsy severity is directly related to the level of neuronal mTORC1 activity . In a TSC/mTOR‐dependent epilepsy mouse model, early treatment with vigabatrin was not able to prevent epileptogenesis, but significantly delayed seizure onset.…”
mentioning
confidence: 99%
See 1 more Smart Citation